Factors controlling tight gas sandstone reservoir quality in the Whicher Range gas field, Southern Perth Basin, Western Australia - Orsini, C.; Rezaee, M. Reza; Wilson, M. (Australian Petroleum Production and Exploration Association, 2011)
The Whicher Range gas field is located south of Busselton in the southern Perth Basin. The focus of this study is the Permian Willespie Formation that has been interpreted as a fluvial system with no marine influence. The formation shows typical tight sand characteristics represented by low porosity (<1–15%) and permeability (<0.01–10 mD). Five wells have been drilled in this field in an extensively faulted anticline. The focus of this extended abstract is to outline factors controlling reservoir quality and lateral reservoir connectivity, and how these contribute to the evaluation of exploration and production potential of this field.